The Role of Personal Values in Marketing and Consumer Behavior - Vinson, Donald E.; Scott, Jerome E.; Lamont, Lawrence M. (Journal of Marketing, 1977)
Can Personal Values be used to assist marketers in determining consumer choice behavior?